Reliability of Point-of-Care International Normalized Ratio Measurements in Various Patient Populations. Issue 1 (March 2020) - Arline, Kim; Rodriguez, Cesar; Sanchez, Krista
Abstract : Purpose: The aim of this study was to determine if the Coagsense point-of-care (POC) instrument provides more reliable international normalized ratio (INR) measurements than Coagucheck XS POC in comparison to the Stago laboratory instrument in different disease states. Methods: This was a prospective study of outpatient warfarin patients comparing venous Stago INR to fingerstick INR on the Coagsense and Coagucheck XS POC meters. Patients were invited to study if they had an of INR 2.0 to 5.0 and had a medical history of antiphospholipid syndrome, hypercoagulable disorder, autoimmune condition, peripheral vascular disease, mechanical heart valve, atrial fibrillation, or deep vein thrombosis/pulmonary embolism/cerebrovascular accident history. Results: Seventy-seven patients were enrolled. Coagsense correlated well (92% of INRs within 20% of Stago, 64% of INRs within 0.2 of Stago, overall INR bias of 0.1 or 4%). Six patients had greater than 20% POC INR bias, which could have resulted in 4 warfarin dosing errors. Coagucheck XS INRs correlated poorly (49% within 20% of Stago, 10% of INRs were within 0.2 of Stago, overall INR bias of 0.66 or 25.7%). Forty-one patients had greater than 20% POC INR bias in all diseases, which could have resulted in 28 warfarin dosing errors. The average Coagucheck XS INR bias (0.46–1.3 INR) increased with each 0.5 increase in laboratory INR, whereas Coagsense bias remained stable (0.1–0.25) as INR increased up to 4.3. Two patients correlated well on Coagucheck XS but not Coagsense. Conclusion: Coagsense correlated better than Coagucheck XS and did not show increasing bias as INR increased. Both POC instruments had higher INR variability in 4 disease states (antiphospholipid syndrome, autoimmune, peripheral vascular disease, and hypercoagulable). Patient-specific laboratory correlations may be needed on each POC device.